Management in elderly patients – questions and controversies - Dzięgielewska, Sylwia (Przewodnik Lekarza/Guide for GPs, 2010)
Thanks to the contemporary medicine an average age increase. Aging is a result of many conditions which are explained throughout many singles aging theories. Understanding the pathomechanism of aging (in a context of pulmonary system) may lead to lowering of growing pathology and better condition among elderly population. It also give better prevention and treatment which often, among elderly, is discriminated because of economy and not controlled properly in our physician practice.